Evaluation of Lipid Profile in the Smokers and Non-Smokers (Academia Journal of Medicine, 2020)
Background: Cigarette smoking leads to increased serum level of total cholesterol, LDL cholesterol, Triglyceride levels and decreased level of anti atherogenic HDL cholesterol. Many studies have shown a dose-dependent relationship between smoking and lipoprotein profile. Hence this study was-taken up to know the lipoprotein pattern in healthy young smokers. Subjects and Methods: Total of hundered healthy smokers and fifty healthy non smokers were included in the study. All the smokers’ subjects were divided in two groups as per the severity of the habit of smoking. Group 1: all those who smoke upto 10 cigarette per day, Group 2: all those who smokemore than 10 cigarette per day. Results: In our study, the mean serum cholesterol of smokers is 205.9 ± 26.1 and that of non-smokers is 165.4 ± 15.2 which is statistically significant Mean HDL-cholesterol is 34.20 ± 4.0 in smokers and 38.40 ± 6.4 in non-smokers, which is statistically significant. Mean LDL-cholesterol is 155.8 ± 29.30 in smokers and 136.70 ± 14.45 in nonsmokers which is statistically significant. Mean Triglyceride level in smokers is 163.28 ± 38.7 and in non-smokers it is 116.72 ± 23.3 which is statistically significant. Conclusion: The mean serum lipid values were significantly higher in smokers except HDL-C which were significantly decreased, as compared to non smokers. There is a linear increase in the levels of serum lipids except HDL-C which shows decrease in the levels with the duration and severity of smoking.
Keywords: Lipid Profile; Smokers; Non-Smokers; Nicotine